2021
DOI: 10.3389/fimmu.2021.745109
|View full text |Cite
|
Sign up to set email alerts
|

A Correlation Between Differentiation Phenotypes of Infused T Cells and Anti-Cancer Immunotherapy

Abstract: T-cell therapy, usually with ex-vivo expansion, is very promising to treat cancer. Differentiation status of infused T cells is a crucial parameter for their persistence and antitumor immunity. Key phenotypic molecules are effective and efficient to analyze differentiation status. Differentiation status is crucial for T cell exhaustion, in-vivo lifespan, antitumor immunity, and even antitumor pharmacological interventions. Strategies including cytokines, Akt, Wnt and Notch signaling, epigenetics, and metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 106 publications
1
10
0
Order By: Relevance
“…Clinically, the injection of CD19pbCAR T cells would likely eliminate CD19 + tumor cells in the treatment of patients with B-cell malignancies. Tcm cells show superior persistence and antitumor immunity in T-cell therapy, making them essential for treatment efficacy (18,19). The present study found that the numbers of Tcm cells was greater in preparations of CD19pbCAR-transduced than of CD19lvCAR-infected T cells.…”
Section: Cd19pbcar T Cell Distribution In Mice and Their Specific Targeting Of Subcutaneous Cd19 + Tumorsupporting
confidence: 48%
See 1 more Smart Citation
“…Clinically, the injection of CD19pbCAR T cells would likely eliminate CD19 + tumor cells in the treatment of patients with B-cell malignancies. Tcm cells show superior persistence and antitumor immunity in T-cell therapy, making them essential for treatment efficacy (18,19). The present study found that the numbers of Tcm cells was greater in preparations of CD19pbCAR-transduced than of CD19lvCAR-infected T cells.…”
Section: Cd19pbcar T Cell Distribution In Mice and Their Specific Targeting Of Subcutaneous Cd19 + Tumorsupporting
confidence: 48%
“…Tcm cells show superior persistence and antitumor immunity in T-cell therapy, making them essential for treatment efficacy ( 18 , 19 ). The present study found that the numbers of Tcm cells was greater in preparations of CD19pbCAR-transduced than of CD19lvCAR-infected T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Ki67 allows the identification of proliferating T cells providing a potential means to identify T cell populations that are responding to any immunotherapy or vaccination ( 48 ). CCR7 was included in this panel to assess T cell trafficking, particularly in lymph node samples, and to monitor T cell differentiation ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that CAR-T cells displaying a “less differentiated profile” (namely, central memory cells), persist and, thus, perform better in vivo . 33 Exhausted T cells may become progressively dysfunctional, and this loss of function is mediated by the up-regulation of inhibitory receptors such as programmed death receptor-1 (PD-1), lymphocyte activation gene-3 (LAG-3), T-cell immunoglobulin-3 (TIM-3), and T-cell immunoreceptor with Ig and ITIM domains (TIGIT). 34 We therefore monitored the expression of these exhaustion markers over time in culture.…”
Section: Resultsmentioning
confidence: 99%